Strategy to develop and manage an aquaponic farm: case of kebun bersama - Ariesto Herman, Bintang; Dung Do, Anh (The Indonesian Journal of Business Administration, 2018)
Abstract. Kebun Bersama is the designation for the aquaponic garden owned by the author. Apart from being a hobby, it also has a high economic value. Its products are organic vegetable and fruit accompanied by source of animal protein in the form of fish, made aquaponic becoming an interesting urban farming system. The problems faced by Kebun Bersama and the aquaponic farmers are; marketing, aquaponic installation costs and production capacity. Today, Kebun Bersama and aquaponic farmers can only utilize community forums as a medium for products and self-introduction to the public, to reach a wider market this is ineffective marketing tool. The initial cost for aquaponic installation is expensive, many people are rethinking for installing aquaponic because of the risk of failure. The third problem is the production capacity, as urban farmers who use limited land and faced the expensive cost of developing the system makes aquaponic farmers distress in the provision of large production. Based on the results of the analysis of the initial condition of aquaponic farmers which is then coupled with the results of interviews and questionnaires, the authors can formulate a new strategy that can support the business of aquaponic farmers. The strategy can be seen in TOWS Matrix and Strategy Diamond in this research. The results of this study indicate that Kebun Bersama must sell aquaponic system installation, training session, and various things related to Aquaponic to get more profit. Then Kebun Bersama should develop an application/system that helps solve marketing problems and has a function as an online training system. Using the system, Kebun Bersama can also create collaboration between aquaponic farmers; a system that can help monitor the activities of aquaponic farmers in a community, as a media sharing progress update and media consultation. Feedback from every consumer will be a marketing tool within the system created by Kebun Bersama. Using this system Kebun Bersama will have benefits in terms of acquisition of new consumers as well as repeat order from existing customers.Â Keywords: Business Strategy, TOWS Matrix, Business Canvas Model, Strategy Diamond, The Lean Startup, Aquaponic